Mothers as facilitators of oral hygiene in early childhood - SIMIN Z. MOHEBBI (IAPD and Blackwell, 2008)
Toothbrushing twice daily is a part of recommended oral self-care and should start as soon as an infant’s teeth erupt 1 . This standard is met for the majority of children in several European Union countries and the USA 2–4 . In Iran, toothbrushing is reportedly practised for only 59% of 3-year-old children 5 . As young children lack the ability to clean their own teeth effectively, parents are recommended to clean their children’s teeth at least until they reach school age 6–8 . Insufficient oral hygiene in terms of presence of visible plaque on anterior teeth of children has been identified as a risk marker for dental caries among young children